MEDIA KONVENSIONAL YANG TERBARUKAN - Ramsiah Tasruddin (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
The presence of new media in this era is a challenge for conventional media owners in transforming to take advantage of the sophistication of available technology. The current competition is not only talking about the writing of a message or news that must meet the element of accuracy alone. However, it is more about understanding what is needed by today's society who are generally interested in flexibility. so that it should be taken into account so that a media can still exist in conveying messages to the audience.